Communicative Orientation of English Language Classes - Mier, Marie Ruffie; Blanco, Gem Aiah B. (FOSTER: Journal of English Language Teaching, 2022)
This study explored on Communicative Orientation of English Language Classes employing the classroom discourse analysis in qualitative research design. The participants of the study are the first year Secondary Education-English students of Bukidnon State University, College of Education. The data gathering was facilitated through the use of Communicative Orientation of Language Teaching observation scheme. The findings revealed that participant organization was mainly student to student in most of the activities with the same assigned task among learners; class management is apparently through discipline, functions, and discourse analysis with limited range of topics that are highly controlled by the teacher; students’ mode of interaction was more on speaking; there is very minimal use of materials for classroom interaction. Further, the participants used L2 than L1; students were noted to have genuine requests and the giving of information were mostly relatively predictable; students’ speeches were to a minimal extent due to the activity type used; the teacher and students showed very limited use of explicit code reaction to errors committed by students; expansion, commenting, and elaboration were found to be prevalent; students were found to have a higher frequency of discourse initiation during classroom interaction; relative restriction of linguistic form was rarely observed; and two other features surfaced which were not predetermined features are on code-switching and the use of fillers. The study revealed that the first-year BSE English students’ speeches are in L2 and to a minimal extent depending on the activity type used by the teacher. Therefore, communicative events such as activity types have direct impact to the use of the different communicative features.